TOURISM LAW (STUDY ON THE DUTCH CEMETRY IN PENELEH SURABAYA) - Michael, Tomy (Doctor of Law Study Program Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2019)
A law is said to be good if the law goes according to its function. By all means is to implement the law in law science. The application of the law is a state characteristic of the law in which the application will be achieved legal objectives consisting of legal justice, legal certainty and legal benefit. Starting from this, the development of tourism in Indonesia, especially in the Dutch cemetry in Peneleh Surabaya does not comply with Act No. 10-2009. This development is also influenced by human resources in this case the government of Surabaya is less concerned about the existence of the Dutch cemetry in Peneleh Surabaya. By doing empirism Research, the results are still low desire of Surabaya city government because the location is not located in the city center